The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1677/jme.1.02143
|View full text |Cite
|
Sign up to set email alerts
|

Separate and synergistic effect of progesterone and estradiol on induction of annexin 2 and its interaction protein p11 in pregnant sheep myometrium

Abstract: To search for myometrial candidate genes regulated by progesterone, we isolated annexin 2 cDNA by subtractive hybridization and cloning. We also examined the effect of estradiol and/or progesterone, individually or combined, on expressions of annexin 2 and its ligand protein, p11 in pregnant sheep intrauterine tissues. Annexin 2 is a Ca 2C -dependent phospholipid-binding protein which interacts with p11 to form a bivalent heterotetramer. The heterotetramer was indicated in the production of prostaglandins thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Previous studies showed that ANXA2 expression could be induced by estrogen in different types of cells, such as myometrium cells (Zhang and Wu, 2007) and macrophages (Hwang et al, 2006). Our data indicated that the estrogen could also act in an autocrine manner to stimulate local ANXA2 expression in theca cells.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies showed that ANXA2 expression could be induced by estrogen in different types of cells, such as myometrium cells (Zhang and Wu, 2007) and macrophages (Hwang et al, 2006). Our data indicated that the estrogen could also act in an autocrine manner to stimulate local ANXA2 expression in theca cells.…”
Section: Discussionsupporting
confidence: 60%
“…Of course, further studies are required to better understanding of this mechanism. 59,61,72,110,112,[114][115][116] In 2007, Qi zhang et al 117 examined the myometrial genes (is the inner layer of the uterine wall which basically contains smooth muscle cells and its main function is stimulation of uterine contraction), which regulated by progesterone or estradiol. In other words, the purpose of this study was to examine the hypothesis of progesterone facilitating role on uterine changes based on decreasing or increasing of genes which are expressed in uterus.…”
Section: S100a10mentioning
confidence: 99%
“…As noted above, however, in nonpregnant animals, progesterone may increase Ca 2+ current density (74). A recent study suggested that another mechanism whereby progesterone controls myometrial contractility is via enhanced annexin 2 expression (91). Annexin 2, with its involvement in the cytoskeleton and association with lipid rafts (see below), can affect phasic contractions (92).…”
Section: Effects On K+ Channelsmentioning
confidence: 99%